Modeled Influence of Land Ice and CO2 on Polar Amplification and Paleoclimate Sensitivity During the Past 5 Million Years. Issue 4 (22nd April 2018) - Stap, L. B.; van de Wal, R. S. W.; de Boer, B.; Köhler, P.; Hoencamp, J. H.; Lohmann, G.; Tuenter, E.; Lourens, L. J.
Abstract: Polar amplification and paleoclimate sensitivity ( S ) have been the subject of many paleoclimate studies. While earlier studies inferred them as single constant parameters of the climate system, there are now indications that both are conditioned by the type of forcing. Moreover, they might be affected by fast feedback mechanisms that have different strengths depending on the background climate. Here we use the intermediate complexity climate model CLIMBER‐2 to study the influence of land ice and CO2 on polar amplification and S . We perform transient 5‐Myr simulations, forced by different combinations of insolation, land ice, and CO2 . Our results provide evidence that land ice and CO2 changes have different effects on temperature, both on the global mean and the meridional distribution. Land ice changes are mainly manifested in the high latitudes of the Northern Hemisphere. They lead to higher northern polar amplification, lower southern polar amplification, and lower S than more homogeneously distributed CO2 forcing in CLIMBER‐2. Furthermore, toward colder climates northern polar amplification increases and consequently southern polar amplification decreases, due to the albedo‐temperature feedback. As an effect, a global average temperature change calculated from high‐latitude temperatures by using a constant polar amplification would lead to substantial errors in our model setup. We conclude that to constrain feedback strengths and climate sensitivity by paleoclimate data, the underlying forcing mechanisms and background climate states have to be taken into consideration. Key Points: Polar amplification and paleoclimate sensitivity ( S ) are intimately linked over the past 5 Myr Similar radiative forcing strength by land ice and CO2 changes has different effects on polar amplification and S Toward colder climates, northern polar amplification increases, causing southern polar amplification to decrease